Sleep Deprivation: Implications for Clinical Practice, Workforce Well-being, and Health System Security-An Updated Review - Kamli, Khalid Khlil Galfan; Mona Rabea Gashoom; Weam Hassan Hamod; Fatima Ali AlhuballL; Radiyah Hassn Almarhoon; Hamedah Mohammed Alhayeki; Sukalnah Ahmed Albanawi; Shrufa Abdullah Ibrahim Attil; Bahyia Ali mohd Koko; Wafa Mnajik Mjmal; Eman Ibrahim Kuahan; Bakheet Abdullah Mbark Alsaffar (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Sleep deprivation is a pervasive yet underrecognized public health issue associated with significant medical, psychiatric, and social consequences. It contributes to metabolic disorders, cardiovascular disease, psychiatric conditions, reduced cognitive performance, and increased accident risk, thereby affecting quality of life and population health. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review aims to summarize updated evidence on the etiology, epidemiology, pathophysiology, evaluation, and management of sleep deprivation, emphasizing implications for clinical practice, workforce well-being, and health system safety. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The article synthesizes current literature addressing the multifactorial nature of sleep deprivation, including medical, psychiatric, behavioral, and environmental contributors. It integrates findings from epidemiological trends, clinical assessments, and therapeutic strategies to provide a comprehensive understanding of the condition. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The review demonstrates that sleep deprivation arises from diverse causes such as sleep disorders, chronic illnesses, psychiatric conditions, lifestyle factors, aging-related sleep architecture changes, and technological influences. Its physiological consequences include neuroendocrine disruption, systemic inflammation, and metabolic dysregulation. Behaviorally, it manifests as cognitive impairment, mood disturbances, daytime sleepiness, and decreased productivity. Effective evaluation integrates history-taking, subjective tools, and objective assessments. Treatment requires a multifaceted approach addressing sleep hygiene, underlying medical and psychiatric conditions, and selective pharmacotherapy. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Sleep deprivation presents substantial clinical and public health challenges. Comprehensive, individualized management and interprofessional collaboration are essential to mitigating its health, psychosocial, and safety consequences.